The Self in Transition: Identity Formation and Crisis in Sally Rooney’s Normal People - Kirana Auliarally Arsyanti; Ruly Indra Darmawan (Universitas Islam Negeri Palopo, 2026)
This study explores the formation and crisis experienced by the main characters, Connell and Marianne, in Sally Rooney's novel Normal People. The problem in this study focuses on how external social pressures and domestic trauma cause the fracture of the subject's identity. Drawing on Jacques Lacan's psychoanalytic theory, specifically the three orders (Imaginary, Symbolic, and the Real), this study employs a descriptive-qualitative method with a literary psychoanalytic approach. The results of the study show that both characters exhibit eccentric identity formation, in which each character's feelings depend entirely on external validation from the Symbolic Order. Connell's crisis is triggered by the destruction of his social status, which causes the failure of the symbolic or automaton function. Meanwhile, for Marianne, this crisis is a cycle of self-deprecation, caused by unprocessed trauma that eventually settles in the realm of reality, which feels foreign and cannot be symbolized through language. This finding concludes that, if others fail to provide a stable label to the subject, the subject's identity is vulnerable to collapse. This study emphasizes that identity is often a fragile construct maintained through uncertain recognition of the external environment.